Antibiotic Prescribing to Patients with Infectious and Non-Infectious Indications Admitted to Obstetrics and Gynaecology Departments in Two Tertiary Care Hospitals in Central India - Anna Machowska; Kristoffer Landstedt; Cecilia Stålsby Lundborg; Megha Sharma (MDPI AG, 2020)
Background: Patients admitted to obstetrics and gynaecology (OBGY) departments are at high risk of infections and subsequent antibiotic prescribing, which may contribute to antibiotic resistance (ABR). Although antibiotic surveillance is one of the cornerstones to combat ABR, it is rarely performed in low- and middle-income countries. Aim: To describe and compare antibiotic prescription patterns among the inpatients in OBGY departments of two tertiary care hospitals, one teaching (TH) and one nonteaching (NTH), in Central India. Methods: Data on patients' demographics, diagnoses and prescribed antibiotics were collected prospectively for three years. Patients were divided into two categories- infectious and non-infectious diagnosis and were further divided into three groups: surgical, nonsurgical and possible-surgical indications. The data was coded based on the Anatomical Therapeutic Chemical classification system, and the International Classification of Disease system version-10 and Defined Daily Doses (DDDs) were calculated per 1000 patients. Results: In total, 5558 patients were included in the study, of those, 81% in the TH and 85% in the NTH received antibiotics (p < 0.001). Antibiotics were prescribed frequently to the inpatients in the nonsurgical group without any documented bacterial infection (TH-71%; NTH-75%). Prescribing of broad-spectrum, fixed-dose combinations (FDCs) of antibiotics was more common in both categories in the NTH than in the TH. Overall, higher DDD/1000 patients were prescribed in the TH in both categories. Conclusions: Antibiotics were frequently prescribed to the patients with no documented infectious indications. Misprescribing of the broad-spectrum FDCs of antibiotics and unindicated prescribing of antibiotics point towards threat of ABR and needs urgent action. Antibiotics prescribed to the inpatients having nonbacterial infection indications is another point of concern that requires action. Investigation of underlying reasons for prescribing antibiotics for unindicated diagnoses and the development and implementation of antibiotic stewardship programs are recommended measures to improve antibiotic prescribing practice.